2017
DOI: 10.1155/2017/8417814
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Time Window of Interest in Ovariectomized Imprinting Control Region Mice for Antiosteoporosis Research

Abstract: This study was performed to determine the optimal window of time during which the properties of osteoporosis are obvious and to explore the best region of interest for microstructural evaluation in antiosteoporosis research in an ovariectomized mouse model by examining changes in micro-computed tomography parameters and serum indices. Ovariectomized mice and sham-operated mice were randomly divided into five groups. At the end of the 4th, 8th, 12th, 16th, and 20th weeks after ovariectomy, the microstructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…At 8 weeks after surgery, when osteoporosis model was established [ 24 ], the body weights of all mice were measured again. Orthodontic appliances were mounted according to our previous studies [ 22 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…At 8 weeks after surgery, when osteoporosis model was established [ 24 ], the body weights of all mice were measured again. Orthodontic appliances were mounted according to our previous studies [ 22 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…We also examined proximal tibia metaphysis trabecular bone; a focus region for many studies. Song et al 35 found most marked effects after eight to 16 weeks of OVX in this region (in eight-week-old mice), which were much less marked later, suggesting that prolongation does not expand the bone losses. Advanced age and the 44-week timescale post-OVX 16 , 35 in our study may not, therefore, be ideal and may underpin the lack of any overt OVX-induced difference.…”
Section: Discussionmentioning
confidence: 92%
“…Song et al 35 found most marked effects after eight to 16 weeks of OVX in this region (in eight-week-old mice), which were much less marked later, suggesting that prolongation does not expand the bone losses. Advanced age and the 44-week timescale post-OVX 16 , 35 in our study may not, therefore, be ideal and may underpin the lack of any overt OVX-induced difference. It is key, however, that we evaluated long-term bisphosphonate effects as our aim was to discern whether this aligned with clinical observations of modified strength and fracture susceptibility.…”
Section: Discussionmentioning
confidence: 92%
“…In our µ-CT analysis, the Tb.Th value was not altered by OVX. Previous reports have also shown that OVX did not significantly decrease the Tb.Th values of the femur and tibia in OVX mice and rats [16,17]. This phenomenon might be due to a rapid change of trabecular structure from a plate-like to a rod-like structure [17].…”
Section: Resultsmentioning
confidence: 99%